MdGH3.6 is targeted by MdMYB94 and plays a negative role in apple water‐deficit stress tolerance. (28th December 2021) - Jiang, Lijuan; Zhang, Dehui; Liu, Chen; Shen, Wenyun; He, Jieqiang; Yue, Qianyu; Niu, Chundong; Yang, Feng; Li, Xuewei; Shen, Xiaoxia; Hou, Nan; Chen, Pengxiang; et al.
SUMMARY: Drought significantly limits apple fruit production and quality. Decoding the key genes involved in drought stress tolerance is important for breeding varieties with improved drought resistance. Here, we identified GRETCHEN HAGEN3.6 (GH3.6), an indole‐3‐acetic acid (IAA) conjugating enzyme, to be a negative regulator of water‐deficit stress tolerance in apple. Overexpressing MdGH3 . 6 reduced IAA content, adventitious root number, root length and water‐deficit stress tolerance, whereas knocking down MdGH3.6 and its close paralogs increased IAA content, adventitious root number, root length and water‐deficit stress tolerance. Moreover, MdGH3.6 negatively regulated the expression of wax biosynthetic genes under water‐deficit stress and thus negatively regulated cuticular wax content. Additionally, MdGH3.6 negatively regulated reactive oxygen species scavengers, including antioxidant enzymes and metabolites involved in the phenylpropanoid and flavonoid pathway in response to water‐deficit stress. Further study revealed that the homolog of transcription factor AtMYB94, rather than AtMYB96, could bind to the MdGH3.6 promoter and negatively regulated its expression under water‐deficit stress conditions in apple. Overall, our results identify a candidate gene for the improvement of drought resistance in fruit trees. Significance Statement: We characterized MdGH3.6 in the response of apple to water‐deficit stress. We found that MdGH3.6 was a direct target of MdMYB94 and a negative regulator of water‐deficit stress tolerance in apple. The negative regulation of water‐deficit stress tolerance may stem from the combined roles of MdGH3.6 in the negative regulation of ROS detoxification and cuticular wax. Overall, our results identify a candidate gene for the improvement of drought resistance in fruit trees.